Ahead of presidential elections, Russia rewrites history and promotes nationalism at schools - Daria Dergacheva (Global Voices, 2023)
New history books and classes called "Important Conversation" are prompting the new nationalist propaganda discourse across schools in Russia.
Russian Federation
Keywords: 2023-10 October